The Effect of Ectoparasites on Hatchery Business of Red Tilapia Oreochromis sp. in Klaten, Central Java - Ramadhani, Dian Eka; Hasna Arafah, Farah; Barunawati Siagian, Tetty; Iqbal Kurniawinata, Mohamad; Rudi, Mad; Fadilla Agustin Rangkuti, Rizky (Journal of Vocational in Aquaculture (JAVA), 2024)
Tilapia fish hatchery in Klaten uses the Dengkeng River as a water source for fish hatchery. The polluted water quality of the Dengklek River has an effect on the increasing number of ectoparasites that can infest tilapia seeds. The purpose of this study to evaluate the effect of ectoparasites on red tilapia in Klaten area, Central Java. This research was conducted at the Freshwater Fish Seed Work Unit, Loka Janti, Klaten. The research sample used red tilapia seeds Oreochromis niloticus measuring ±4-6 cm. Fish sampling was carried out randomly at the Freshwater Fish Seeding Work Unit Loka Janti, Klaten. Sampling was taken as many as 5 samples from 28 semi-permanent ponds. Physical and ectoparasite examinations were carried out on tilapia seeds. The data analyzed included water quality, epidemiology, parasite count measurements, specific growth rates, financial values, and Sensitivity Analysis. Ectoparasites can affect tilapia cultivation activities and cause losses. Fortunately, the ectoparasites in Loka Janti did not cause harm. Tilapia hatchery harvest size 2–3 cm with a selling price of Rp75.00 fish-1 resulted in an income of Rp426.062.70,00 and a profit of Rp71.814.554,00. The R/C ratio obtained is 1,20, and the payback period is 4,4 years.